Floral and reproductive biology of Vaccinium meridionale (Ericaceae) in the Eastern Andes of Colombia. - Chamorro, Fermín J.; Nates-Parra, Guiomar (Revista de Biología Tropical, 2015)
Vaccinium meridionale is a wild plant producing edible fruits in the mountain areas of Northern South America. However, the fruits of this species has been under an unsustainable extraction and there is a growing interest of establishing this species as a crop; nevertheless, the information about its breeding system is scarce, which is essential for its sustainable management and conservation. This research aimed to study the floral and reproductive biology of V. meridionale in natural conditions, and to analyze the importance of pollinators on its reproduction, in two wild populations of V. meridionale in the states of Cundinamarca and Boyacá, in the Oriental Cordillera of Colombia. For this, we have made different observations and experiments to describe its flower morphology, floral phenology, pollen viability, stigma receptivity, pollen-ovule ratio and nectar production. To study its reproductive system, we performed experiments of flower emasculation, pollinator exclusion and hand pollination (self-and cross-pollination). We found that although the flowers have poricidal anthers, the release of pollen could occur easily without vibration. V. meridionale shows a large floral display, long floral longevity and has female-biased nectar production. The pollen-ovule ratio was of 571±133, which classified the species as facultative xenogamy. This result agreed with the pollination experiments because the plants produced fruits by agamospermy, selfing and outcrossing. However, we registered a strong inbreeding depression, observed in high rates of fruit abortions, after self-pollination. Unlike of self-pollinating fruits, the plant retains those produced by cross-pollination since its formation. The floral traits showed by this species are mechanisms to favor a more diverse guild of floral visitors than only insects able to buzz-pollination. In addition, these floral traits may enhance the pollination probability, and reduce geitonogamy. Moreover, the inbreeding depression suggests that V. meridionale promotes outcrossing as its main reproductive strategy. Therefore, pollinators, particularly bees, are essential for this species reproduction and conservation, and are critical in the maintenance of its genetic variability and fruits production.